The role of implementing supplier relationship strategies, relationship with customer, and information sharing on company performance - Afrilia, Eka; Ratihsabella, Inesa Nining (Universitas Ahmad Dahlan, 2023)
Purpose-In this study, the effects of information sharing, customer relations, and supplier relationship strategies on company performance are investigated. Design/Methodology/Approach-The study's sample consists of workers of Bank Rakyak Indonesia, which is situated in Yogyakarta's Special Region. 60 workers served as responders in the study, providing a sample size. This research data is acquired using the Smart PLS analysis program in order to get the intended outcomes. Findings-Empirical results indicate that supplier relationship strategies and information sharing positively impact company performance. Conversely, relationship with consumers who have a negative impact on company performance. Research limitations/implications- This study's scope is restricted to operational factors that impact company performance, such as customer relationships, supplier relationship strategies, and information sharing. The study's findings can be utilized by businesses as a foundation for assessment to optimize variables that may impact their performance. Originality/value- It can be argued that there is still a dearth of research on the performance of banking institutions operating in the Special Region of Yogyakarta. No prior studies have addressed the performance of these institutions with regard to operational factors like supplier relationship strategies, customer relationships, and information sharing.